Justification Of Thrust Bearings Parameters For Increasing The Reliability Of Downhole Pumps - Pulatov T.R., Asanov S., Hoshimov A.A (International Journal of Advanced Science and Technology, 2020)
This article provides a study of factors affecting the reliability and durability of thrust bearings in electric centrifugal pumps of the ECW type. For these factors, a number of analytical equations are presented that can be used in determining the parameters for friction pairs of thrust bearings of turbine generators of hydroelectric stations. The methodology for testing to determine the operational roughness of friction pairs established after the end of the running-in process is described in detail. During of the experiments, values of roughness parameters differing from the initial values were obtained. The initial production of surfaces of friction pairs with parameters closer to operational gives a faster transition to equilibrium roughness, a decrease in initial wear and an increase in the reliability of friction pairs. It is recommended to produce sliding friction pairs of downhole pumps with roughness parameters Ra=0.31-0.37 μm.